THE RELATIONSHIP BETWEEN KNOWLEDGE AND DIET COMPLIANCE TOWARDS THE STABILITY OF BLOOD SUGAR LEVELS IN DIABETES MELLITUS PATIENTS TYPE II IN THE WORK AREA OF PAMULANG COMMUNITY HEALTH CENTER (Proceedings OPTIMAL, 2025)
Blood sugar levels are the amount of glucose circulating in the blood. The levels are influenced by various types of enzymes and hormones, the most important of which is the insulin hormone. Based on the results of the 2023 Banten Province Health Profile report, for the South Tangerang City (TANGSEL) area, the number of DM sufferers was 52,488 people. Research Objectives: To determine the relationship between the level of knowledge and dietary compliance in type II DM sufferers at the Pamulang Health Center. Research Methodology: The type of research used is analytical observation with a cross-sectional research design where researchers want to analyze the relationship between knowledge and dietary compliance with blood sugar levels in patients with Diabetes Mellitus. The respondents in this study were 84 with data collected using a questionnaire. Research Results: Shows that Diabetes Mellituh sufferers who have sufficient knowledge are 15 respondents (17.9%), and normal blood sugar levels are 29 respondents (34.5%), analysis using the chi-square test obtained a value (p- value < α = 0.05) which means Ha is accepted and Ho is rejected. Diabetes Mellituh sufferers who have sufficient compliance are 13 respondents (15.5%), and normal blood sugar levels are 30 respondents (35.7%), analysis using the Chi-square test obtained a value (p-value = 0.000) so that (p-value < α = 0.05) which means Ha is accepted and Ho is rejected. Conclusion: this study found that there is a relationship between knowledge and dietary compliance to stable blood sugar levels in the Pamulang Health Center work area. Suggestion: This study is expected to be useful for respondents regarding the importance of knowledge and dietary compliance in order to maintain stable blood sugar levels.